S3 Guideline for the treatment of psoriasis vulgaris, update – Short version part 2 – Special patient populations and treatment situations. (5th June 2018) - Nast, Alexander; Amelunxen, Lasse; Augustin, Matthias; Boehncke, Wolf‐Henning; Dressler, Corinna; Gaskins, Matthew; Härle, Peter; Hoffstadt, Bernd; Klaus, Joachim; Koza, Joachim; Mrowietz, Ulrich; Ockenfels, Hans‐Michael; et al.
Summary: The German guideline for the treatment of psoriasis vulgaris was updated using GRADE methodology. The guideline is based on a systematic literature review completed on December 1, 2016, and on a formal consensus and approval process. The second part of this short version of the guideline covers the following special patient populations and treatment situations: tuberculosis screening before and during psoriasis treatment, choice of psoriasis treatment for individuals wishing to have children, as well as during pregnancy and breast‐feeding, and patients with joint involvement and vaccinations. In addition, recommendations on the choice of treatment are presented for patients with the following comorbidities: hepatitis and other hepatic impairment, HIV, malignancies, neurological and psychiatric disorders, ischemic heart disease and congestive heart failure, diabetes mellitus, renal impairment and inflammatory bowel disease.